Belonging and Social Integration as Factors of Well-Being in Latin America and Latin Europe Organizations - da Costa, Silvia; Martínez-Moreno, Edurne; Díaz, Virginia; Hermosilla, Daniel; Amutio, Alberto; Padoan, Sonia; Méndez, Doris; Etchebehere, Gabriela; Torres, Alejandro; Telletxea, Saioa; García-Mazzieri, Silvia (Frontiers in Psychology, 2020)
Background Studies and meta-analyses found individual, meso and micro-social factors that are associated with individual well-being, as well as a positive socio-emotional climate or collective well-being. Aim This article simultaneously studies and examines these factors of well-being. Method Well-Being is measured as a dependent variable at the individual and collective level, as well as the predictors, in three cross-sectional and one longitudinal studies. Education and social intervention workers (N = 1300, K = 80) from Chile, Spain and Uruguay participate; a subsample of educators (k = 1, n = 37) from the south central Chile and from Chile, Uruguay and Spain (n = 1149); workers from organizations in Latin America and Southern Europe, military cadets from Argentina (N < 1000); and teams (K = 14) from Spanish companies. Results Individual and collective well-being indicators were related, suggesting that the emotional climate as a context improves personal well-being. Individual factors (emotional creativity and openness and universalism values), psychosocial factors (low stress, control over work and social support supervisors and peers) were positively associated with personal well-being in education and social intervention context. Organizational dynamic or transformational culture is directly and indirectly associated with individual well-being through previously described psychosocial factors. Group processes such as internal communication and safe participation, task orientation or climate of excellence as well as leadership style that reinforces participation and belonging, were positively associated with collective well-being in labor and military context and predict team work socio-emotional climate in a longitudinal study- but were unrelated to individual well-being. Transformational leadership plays a mediating role between functional factors and social-emotional climate in work teams. Organizational role autonomy, functional organizational leadership, integration and resources were associated with collective well-being in organizations. Organizational leadership moderates the relationship between task orientation and collective well-being in military context. Conclusion Individual and microsocial factors influence personal well-being. Meso level factors favorable to well-being through processes which reinforce social belonging, influence directly collective well-being and indirectly personal well-being. Leadership that reinforces participation and belonging play a central role for emotional climate. Stress and emotional climate playing an important pivotal role for psychological well-being.